2014
DOI: 10.1039/c4an00999a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent sensors for the basic metabolic panel enable measurement with a smart phone device over the physiological range

Abstract: The advanced functionality of portable devices such as smart phones provides the necessary hardware to potentially perform complex diagnostic measurements in any setting. Recent research and development have utilized cameras and data acquisition properties of smart phones to create diagnostic approaches for a variety of diseases or pollutants. However, in concentration measurements, such as blood glucose, the performance of handheld diagnostic devices depends largely on the sensing mechanism. To expand measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…In the absence of analyte, the ionophore is protonated, but upon selective binding of the analyte, the dye deprotonates to maintain the charge balance in the particle, resulting in a concentration-dependent change in optical properties. This approach has been used to measure common blood panel analytes, both in vitro 66 Saliva has a long history of use in clinical diagnostics due to the ease of sample collection (swab or passive drool) and the wide variety of both host biomarkers and those associated with infection. A key issue with saliva, as shown in Table 1, is the extreme range of fluid viscosity, which is a key challenge for device engineering.…”
Section: Biosensor Application With Commonly Sampled Fluidsmentioning
confidence: 99%
“…In the absence of analyte, the ionophore is protonated, but upon selective binding of the analyte, the dye deprotonates to maintain the charge balance in the particle, resulting in a concentration-dependent change in optical properties. This approach has been used to measure common blood panel analytes, both in vitro 66 Saliva has a long history of use in clinical diagnostics due to the ease of sample collection (swab or passive drool) and the wide variety of both host biomarkers and those associated with infection. A key issue with saliva, as shown in Table 1, is the extreme range of fluid viscosity, which is a key challenge for device engineering.…”
Section: Biosensor Application With Commonly Sampled Fluidsmentioning
confidence: 99%
“…Then, lots of groups attempted to use smartphone-based spectrophotometry directly to quantify fluorescent intensity in biochemical detections Awqatty et al, 2014;Dutta et al, 2014;Fronczek et al, 2014;Hossain et al, 2014;Noor and Krull, 2014;Petryayeva and Algar, 2014;Yu et al, 2014). For instance, Fronczek et al reported a rapid protocol using paper-based microfluidic for fluorescent identification of the nucleic acids of Salmonella on smartphone (Fronczek et al, 2014).…”
Section: Fluorescence Biosensors On Smartphonementioning
confidence: 98%
“…© 2017. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/ Awqatty et al, 2014). Lasers have the advantage that their light is monodirectional and powerful, and can penetrate the sample without losing too much signal on the way.…”
Section: Luminescence and Fluorescence Detectionmentioning
confidence: 99%
“…Moreover, LED adapters are simpler, amenable to miniaturization and portable. This is another case in which the Arduino controller can be integrated into the system, as exemplified by Awqatty et al, 2014. They controlled the LED light emission using the mobile phone itself as energy source; as such, no external batteries were required.…”
Section: Luminescence and Fluorescence Detectionmentioning
confidence: 99%